Biomedical applications of mesoporous ceramics : drug delivery, smart materials, and bone tissue engineering /: drug delivery, smart materials, and bone tissue engineering. ([2013]) - Vallet-Regí, María; Manzano Garcia, Miguel; Colilla, Montserrat
No abstract available